Cell fine structure and phylogeny of Parvodinium: towards an ultrastructural characterization of the Peridiniopsidaceae (Dinophyceae). Issue 2 (3rd April 2023) - Pandeirada, Mariana S.; Craveiro, Sandra C.; Daugbjerg, Niels; Moestrup, Øjvind; Calado, António J.
Abstract: Recent molecular phylogenies that include species of Parvodinium revealed as its closest relatives the genera Peridiniopsis, Palatinus and Johsia . The clade containing these taxa is currently recognized as a family, Peridiniopsidaceae. The affinity between the members of Peridiniopsidaceae cuts across traditional boundaries based on features of the amphiesma, most notably the presence or absence of an apical pore complex. Detailed descriptions of the fine structure of Peridiniopsis and Palatinus are available from TEM studies of their type species. Here we provide a description in comparable detail of a species of the Parvodinium umbonatum–inconspicuum complex, which includes the type of the genus. The cells had an apical fibrous complex essentially similar to those described from other peridinioids prepared with comparable fixations. The pusular system was extensive and included areas with different aspects: an area with a sheet-like vesicle along the mid-right side of the cell, a ventral portion with ramified and anastomosed tubes and a somewhat flattened tube attached to the transverse flagellar canal. The most remarkable feature was the microtubular strand that extended from a ventral, protruding peduncle to the anterior part of the epicone, around an accumulation body, and came around along a more dorsal position toward the ventral side. This long microtubular strand of the peduncle (MSP) was reminiscent of the one described from Peridiniopsis borgei, both by its extension and looping path, and by the breaking up of the strand of microtubules into smaller portions with a wavy appearance; and contrasted with the reduced MSP of Palatinus apiculatus . The fine-structural features currently known from Peridiniopsidaceae are summarized. Members of the family include a flagellar apparatus with four microtubule-containing roots associated, the basal bodies inserted close to each other, nearly at right angles and a three-armed fibrous connective between root 1 and the transverse basal body. HIGHLIGHTS: Detailed fine structure of Parvodinium (of P. umbonatum–P. inconspicuum complex). Comparative analysis of the ultrastructure of Parvodinium and other Peridiniopsidaceae. Summary of ultrastructural features of the family Peridiniopsidaceae.